2020
DOI: 10.1044/2019_jslhr-19-00099
|View full text |Cite
|
Sign up to set email alerts
|

How Does Our Voice Change as We Age? A Systematic Review and Meta-Analysis of Acoustic and Perceptual Voice Data From Healthy Adults Over 50 Years of Age

Abstract: Purpose Approximately 30% of adults over the age of 50 years present with altered vocal function. Our understanding of how these changes manifest acoustically and perceptually is derived from relatively modest-sized studies using a diversity of tools. Voice changes can arise from the onset of disease or disorder, but also age-related physiological changes, which may not reflect pathology as such. Here, we bring together data on acoustic, perceptual, and instrumental assessments (electroglottography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 83 publications
1
18
0
Order By: Relevance
“…A disproportionately elevated GA for a given IAD implies bowing of the vocal folds. Although vocal fold bowing can also occur with ageing due to vocal fold atrophy [22], we showed that the mean/effective maximum IAI is increased in pwPD when compared to age-matched controls. The mean/effective maximum IAI is more…”
Section: Plos Onementioning
confidence: 52%
“…A disproportionately elevated GA for a given IAD implies bowing of the vocal folds. Although vocal fold bowing can also occur with ageing due to vocal fold atrophy [22], we showed that the mean/effective maximum IAI is increased in pwPD when compared to age-matched controls. The mean/effective maximum IAI is more…”
Section: Plos Onementioning
confidence: 52%
“…With respect to the role of age in the prediction performance, the features in this study were able to predict age with a comparable if slightly lower performance to other published approaches to investigate the prediction of age using prosodic features [89, 90]. Research on changes of prosody in aging indicates higher scores of hoarseness, instability and breathiness in higher age [91, 92], reflected by a diminished harmony to noise ratio [93]. Moreover, with increasing age, the subglottal pressure decreases in line with a decrease in overall muscle mass, and proband compensate this with increased expiratory airflow [94].…”
Section: Discussionmentioning
confidence: 90%
“…Voice asthenicity (A3) and breathiness (B3) were observed in 90% of the diagnosed men. Martins et al, 18 Rojas et al, 21 and Rosow et al 23 also used the GRBAS scale in the assessment of Presbyphonia emphasizing its diagnostic usefulness.…”
Section: Discussionmentioning
confidence: 99%